A Phase I Clinical Study Comparing the Tolerance, Immunogenicity, and Pharmacokinetics of Proposed Biosimilar BAT1806 and Reference Tocilizumab in Healthy Chinese Men - Zhang, Hong; Wang, Hong; Wei, Haijing; Chen, Hong; Liu, Jingrui; Li, Cuiyun; Zhu, Xiaoxue; Li, Xiaojiao; Yu, Jinchen; Zhou, Yinbo; Yang, Xiaolei; Wang, Zhaohe; et al. (Frontiers in Pharmacology, 2021)
Objective: The study aimed to explore the bioequivalence of a proposed biosimilar BAT1806 to its reference products marketed in the EU and US (RoActemra-EU and Actemra-US) among healthy Chinese men. The tolerance, immunogenicity, and pharmacokinetics (PK) of the three drugs were also investigated. Methods: In this randomized, double-blind, single-dose, three-arm, parallel study, a single-dose of 4 mg/kg of the reference products, or the biosimilar was administered to the participants. The participants were followed up for 57 days, and PK, immunogenicity, and tolerance evaluations were completed during this period. Results: The PK parameters were similar in all three groups: BAT1806 (n = 45), RoActemra-EU (n = 42), and Actemra-US (n = 42). The 90% confidence intervals (CIs) for the ratios of Cmax, AUC0–t and AUC0–∞ were 86.90–104.41% for BAT1806 vs. RoActemra-EU, 91.70–106.15% for BAT1806 vs Actemra-US, and 90.04–105.53% for Actemra-US vs RoActemra-EU. For all comparisons, the 90% CIs for the Cmax, AUC0–t, and AUC0–∞ were within the predefined bioequivalence limit of 80.00–125.00%. The intersubject variability ranged from 14.5% to 21.5%, which was considerably low. Among the participants, 19 (42.2%), 10 (23.8%), and 12 (28.6%) from the BAT1806, RoActemra-EU, and Actemra-US groups were, respectively, found to be positive for anti-drug antibodies, while 14 (31.1%), nine (21.4%), and 12 (28.6%) were positive for neutralizing antibodies. Nevertheless, these antibodies did not affect the drug concentrations, and the outcomes in the bioequivalence tests were similar after sensitivity analysis. Treatment-related and treatment-emergent adverse events (TEAEs) were recorded in 27, 34, and 32 participants in the BAT1806, RoActemra-EU, and Actemra-US groups, respectively. The most common treatment-related adverse events observed were a decrease in neutrophil, and white blood cell counts. Conclusion: The PK characteristics of BAT1806 were similar to those of the reference products, RoActemra-EU and Actemra-US. Both BAT1806 and the reference products exhibited low intersubject variability and similar safety profiles. Clinical trial registration number:http://www.chinadrugtrials.org.cn/index.html, CTR20180039; https://clinicaltrials.gov/NCT03606876